Management and Performance in Mission Driven Organizations - Cantarelli, Paola. author. aut Link
VII, 114 p. 1 illus.
Keywords: Management scholars worldwide increasingly capitalize on theoretical models and research designs from the behavioural sciences to close the implementation gap in mission-driven organisations. This book aims at synthesising the theoretical frameworks and evidence that has flourished over the past decades in order to advance the scholarly debate and the implications for practice in the domains of performance management, information systems, investments strategies, people administration, and change and innovation. It provides meaningful insights to tackle real-world challenges that organizations and their managers face on a daily basis; including why two managers can make radically different decisions in front of the same information, which cognitive traps most often get in the way of good performance management, and how managerial interventions can limit such errors and variability. Paola Cantarelli is Assistant Professor in the Management and Healthcare Lab, Institute of Management, Sant’Anna School of Advanced Studies, Italy. Her research focuses on the use of behavioral sciences to improve management practices and performance in mission-driven organizations.